Tanggapan Diskusi Kelompok Forum Guru SMP Terhadap Penerapan Adat Bersendi Syara’ Syara’ Bersendi Kitabullah dalam Pembelajaran - Astalini Astalini; Darmaji Darmaji; Dwi Agus Kurniawan; Rido Ilham Widodo; Siti Rohana (Journal Evaluation in Education (JEE), 2022)
Purpose of the study: Students develop according to the nature of nature and the times. This causes the development of the times to have an influence on the development of students. One of the impacts of the current developments is the loss of awareness to love and even know local wisdom in the environment around students. Therefore, the implementation of local wisdom in classroom learning is essential to do. In this study, an evaluation of the response of the educators to the training on the application of the adat bersendi syara' syara' bersendi Kitabullah was carried out in learning. Methodology: This research used a descriptive quantitative method. 20 educators at SMPN 30 Muaro Jambi were the subjects of this study. Main Findings: The results of the research showed that educators had a positive response to the training on applying the adat bersendi syara' syara' bersendi Kitabullah in learning. These results are indicated by the average above 3 in the table. Therefore, it was found that the educators at SMPN 30 Muaro Jambi positively responded to the training on applying the adat bersendi syara' syara' bersendi Kitabullah in learning. Novelty/Originality of this study: The research illustrates that it is essential to conduct cultural-based learning training in schools, especially for teachers. Because it is through education and learning in the classroom that students gain an understanding of the culture around them